Development Center of Minapolitan Area in Wajo District - Kumala Dewi, Yashinta; Safruddin, Safruddin; Zainuddin, Mukti (Hasanuddin University, 2024)
Regional development with a Minapolitan concept is part of the marine and fisheries industrialization policy strategy which aims to realize accelerated increases in the income of cultivators, fishermen, processors, and marketers by integrating upstream and downstream production systems to increase the scale and quality of production, productivity, competitiveness and added value for sustainable marine and fisheries resources. The Minapolitan program is designed to increase the competitiveness of fisheries commodities which is then targeted to increase regional competitiveness and reduce the gap between urban and rural areas. This activity is intended to formulate a development center for the Minapolitan area of ​​Wajo District which will become the basis for preparing technical work plans for related agencies. Based on field results, it was found that the marine and fisheries resource potential of Wajo District was mapped into two resource potential zones, namely (1) the coastal subdistrict area (Bola, Takkalalla, Sajoanging, Penrang, Keera and Pitumpanua subdistricts) which is directly connected to the waters of Bone Gulf for the utilization of potential resources of capture fisheries and aquaculture (marine cultivation and pond cultivation); and inland fisheries areas, especially in the Tempe lake area (Sabangparu, Tempe, Tanasitolo and Belawa subdistricts). Utilization of the potential of the coastal areas of the District of Wajo, with its characteristics of an open water area directly bordering Gulf of Bone, has more potential for the development of capture fisheries, marine aquaculture, and brackish/pond cultivation with the superior commodities of seaweed and mangrove crabs as well as coastal ecotourism. Meanwhile, the Tempe Lake area is more geared towards fishing, cultivating freshwater fish and limited area management for ecotourism activities.